Dynamical System of Tuberculosis Considering Lost Sight Compartment - Heizlan Muhammad; Paian Sianturi; Endar H. Nugrahani (International Journal of Engineering and Management Research, 2019)
In this study, a model for the tuberculosis infection considering vaccination and lost-sight compartement is formulated. there are six populations in this model, Susceptibled, vaccinated, exposed, lost sight, infected, and recovered. The lost sight populations are infected but do not get any treatment and still can spread the tuberculosis, the infected population are infected but already got a treatment and no longer spread the tuberculosis. The local stability are obtained by analyzing the epidemic threshold . The result shows that the disease-free equilibrium is locally asymptotically stable when the condition <1 is satisfied, and the unique endemic equilibrium exist and it is locally asymptotically stable if >1 is satisfied. The numerical simulation are also performed to support the analytical result.